Principles of physical factor selection in the early postoperative period of breast cancer treatment: a randomized controlled study - Inna S. Evstigneeva (Вестник восстановительной медицины)
INTRODUCTION. Current models of onco-rehabilitation do not consider the patient’s functional impairment during combined treatment until the patient becomes incapacitated and the impairment develops into a chronic condition.